CLASSIFICATION OF FOCUSES AND MECHANICAL TRANSMISSION OF PLANT VIRUSES - Qalandarova Madina Andreyevna; Nigmatullayev Bakhtiyor Alimovovich; Mardonov Fozilbek Mardonovich (American Journal of Applied Science and Technology, 2024)
Currently, as a result of the development of many lands, the primary virus foci have decreased. As a result, new relationships between cultivated and wild plants, pathogens and vectors have emerged. To some extent, these relations are characterized by the concept of natural foci. Because some viruses specialize in a narrow range of plants, they do not spread at all in natural foci. Therefore, studying both theoretical and practical aspects of work in this direction with the help of new, modern methods and technologies is one of the urgent tasks before us in the near future. To date, there is information on several characteristics of all studied tomato, tobacco, turnip, rapeseed, radish, potato, alfalfa, cotton, corn, and bell pepper viruses in Uzbekistan. But there is no information about their natural foci and groups, and how they slowly infect cultivated plants and the emergence of new virus foci, and they have not been studied until now. Taking this into account, we can identify the natural foci of some viruses studied in Uzbekistan and see the ways of their transmission, especially mechanical transmission.